Complete Genome Sequence of Streptococcus iniae YSFST01-82, Isolated from Olive Flounder in Jeju, South Korea - Rajoo, Sasikumar (Genome Announc, 2015)
Streptococcus iniae is associated with morbidity in commercial fish species, especially in olive flounders (Paralichthys olivaceus), and was recently identified as an emerging human pathogen. Here, we report the complete 2.09-Mb genome sequence of S. iniae strain YSFST01-82, isolated from an olive flounder with streptococcosis disease in Jeju, South Korea.